1992
DOI: 10.1099/00221287-138-1-139
|View full text |Cite
|
Sign up to set email alerts
|

IS902, an insertion element of the chronic-enteritis-causing Mycobacterium avium subsp. silvaticum

Abstract: An insertion sequence element of Mycobacterium avium subsp. silvaticum was isolated and its complete nucleotide squence determined. IS902 is 1470 bp in size and is repeated 1&12 times per genome. An open reading frame of 1200 bp was identified, encoding a protein product of Mr 43932. This protein is highly similar to the predicted proteins of IS900 of Mycobacterium paratuberculosis, IS116 of Streptomyces clavuligerus and IS1 10 of Streptomyces coelicolor. IS902 lacks terminal inverted repeats and flanking dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

1993
1993
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 24 publications
1
52
0
2
Order By: Relevance
“…paratuberculosis genome. Previous studies have suggested that the arrangement at some loci is one in which IS900 inserts between the RBS and start codon of the target gene such that the hed ORF, which contains its own start codon within IS900, comes under the control of the upstream host promoter (Tizard et al, 1992 ;Doran et al, 1997). In the present paper, we have used the term ' hed orientation ' to describe the situation in which the predicted direction of genomic transcription at the target locus is in the same direction as hed.…”
Section: Abbreviation : Mpil Multiplex Pcr Of Is900 Locimentioning
confidence: 99%
See 2 more Smart Citations
“…paratuberculosis genome. Previous studies have suggested that the arrangement at some loci is one in which IS900 inserts between the RBS and start codon of the target gene such that the hed ORF, which contains its own start codon within IS900, comes under the control of the upstream host promoter (Tizard et al, 1992 ;Doran et al, 1997). In the present paper, we have used the term ' hed orientation ' to describe the situation in which the predicted direction of genomic transcription at the target locus is in the same direction as hed.…”
Section: Abbreviation : Mpil Multiplex Pcr Of Is900 Locimentioning
confidence: 99%
“…avium strain 104 genome, but a  search with ORFs either side of locus 6 showed homology (38 % identity) to a polyketide synthase of M. tuberculosis (pks17 : Rv1663) and a transcription regulator (38 % identity) in S. coelicolor (tetR : SCJ11.45c). Loci 4, 6, 8 and 11 corresponded to the IS900 insertions previously described as pMB22, pMBJ3, pMBJ2 and pMBL15, respectively (McFadden et al, 1987 ;Green et al, 1989 ;Moss et al, 1992 ;Hernandez Perez et al, 1994). In addition, although minor sequence differences were observed, locus 3 was equivalent to pMB55.…”
Section: Blast Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…During the recent genetic analysis of several mycobacterial species, various repetitive DNA elements have been found; many of them have features in common with typical IS elements (Cirillo et al, 1991;Eisenach et al, 1990;Green et al, 1989;Kunze et al, 1991 ;Martin et al, 1990;McAdam et al, 1990;Moss et al, 1992;Patel et al, 1990;Thierry et al, 1990;Woods & Cole, 1990). Transposable elements can be of value as genetic tools.…”
Section: Introductionmentioning
confidence: 99%
“…8 The other 2 M. avium subspecies also appear to have 1 or 2 unique sequences (IS901 and IS902) although these do not always seem to be present. 12,14 A general prerequisite for a sensitive and specific serologic test is a specific test antigen. Mycobacterium a. paratuberculosis has a wide range of antigenic determinants, some of which may also be found in Eschericia coli, 7 Nocardia asteroides, corynebacteria, and other mycobacteria.…”
Section: Comparison Of Two Enzyme-linked Immunosorbent Assays For Sermentioning
confidence: 99%